Research Letter: Antihypertensive Drugs Market in India: An Insight on Size, Trends, and Prescribing Preferences in the Private Health Sector, 2016–2018. Issue 1 (2nd August 2021) - Sahoo, Swagata Kumar; Pathni, Anupam Khungar; Krishna, Ashish; Moran, Andrew E.; Cohn, Jennifer; Bhatia, Sanchit; Maheshwari, Nilesh; Sharma, Bhawna
Background: India has a high burden of hypertension. While the private sector provides 70% of out-patient care in the country, a significant proportion of patients seeking care from the public sector buy drugs from private markets. This study aimed to describe India's private sector antihypertensive drugs market at the national and state levels over 2016–2018. Methods: Antihypertensive drugs sales in India from 2016–2018 were analysed using a large nationally representative dataset for the private pharmaceuticals market. In addition, data for five states (Punjab, Madhya Pradesh, Kerala, Telangana, and Maharashtra) that were the foci of a large hypertension control program were studied. Results: The Indian hypertension drug market grew at a rate of 6.9% from 2016 to 2018 with a total of 21, 066 million pills sales in 2018. Single-pill combinations (SPCs) contributed to 39.1% of total sale volumes. The market comprised of 182 different antihypertensive drugs including 134 SPCs. Total volume of sales covered a maximum of 26% of treatment need for the estimated population with hypertension. Two-drug SPCs had the highest market share (36%), followed by calcium channel blockers (18%), beta-blockers (16%) and angiotensin receptor blockers (14%). Among SPCs, amlodipine+atenolol had highest sales (9.8%). Twenty-five drugs, a mix of single drugs and SPCs, accounted for 80% of total sales. There were large state-to-state variations in sales per capita, preferred therapeutic classes and drugs. Conclusions: Despite the large antihypertensive drugs market, there exists a high unmet need for treatment in India. Inter-state differences in product sales indicate variable treatment practices, underscoring the need for private sector engagement to improve hypertension care practices aligned with national and international guidelines. SPCs contributed to a large share of the private market and inclusion of select antihypertensive SPCs in the national list of essential medications should be considered for the public health system.